Momentos de protección de luz solar en el rendimiento en Lactuca sativa L. en un sistema hidropónico. Loreto - Peña Araujo, Anthony Johau (2024)
This study investigated the effect of exposure to different moments of sunlight on the agronomic characteristics and yield of Lactuca sativa L. (lettuce) cultivation in a hydroponic system in the Loreto region. A completely randomized experimental design with ten repetitions was employed, using floating root hydroponic boxes. Treatments included different moments of sunlight exposure: 6.0 am - 12.0 pm (6 h), ----(6 h), (0 h), and 6.0 am - 6.0 pm (12 h), using 50% shade mesh for each treatment. All analyzed variables, such as plant height, root length, plant width, number of leaves, root weight, total leaf weight, and total plant weight, showed statistical significance based on the moment of sunlight exposure. Particularly, a statistically significant difference (p < 0.01) was observed in the treatment of shading all day, where the total leaf weight reached 85.92 g and the total plant weight reached 94.40 g, while shading from 6.0 am to 12 pm showed the lowest values with 45.55 g and 53.90 g, respectively. These results highlight the importance of proper sunlight management to optimize the growth and yield of lettuce cultivation in hydroponic systems in the Loreto region.